SADDAM'S BOMBMAKER : THE DARING ESCAPE OF THE MAN WHO BUILT IRAQ'S SECRET WEAPON - Khidhir Hamza, author 644650; Stein, Jeff, author 644651 (New York : Simon & Schuster, 2001)
The author who spent twenty years developing Iraq's atomic weapon, recounts his life in Saddam Hussein's inner circle and his daring flight to the West. The book delves into the darkest corners of a regime ruled by a volatile, brutal leader, Dr. Hamza, the only defector who has lived to write a firsthand portrait of Iraq, also presents an unprecedented portrait of Saddam -- his drunken rages, his women, his cold-blooded murder of underlings, and his unrivaled power. If pushed to the wall, Saddam will use the bomb that Dr. Hamza helped create. This is an account of what he endured in Iraq to his harrowing flight across three continents and his first encounter with skeptical CIA agents who turned him away